Environmental evidence from early urban Antwerp: New data from archaeology, micromorphology, macrofauna and insect remains. (1st December 2017) - Crabtree, Pam J.; Reilly, Eileen; Wouters, Barbora; Devos, Yannick; Bellens, Tim; Schryvers, Anne
Abstract: Recent excavations along the Jordaenskaai, in the medieval burg area in central Antwerp, have provided a unique opportunity to explore the archaeology, economy, and environmental context of early medieval Antwerp. This multidisciplinary project examined structures and features that are radiocarbon dated to 760–970 CE in order to gain a better understanding of the use of human and environmental resources and the use of space at the dawn of this trade town. By combining micromorphology and the analyses of both the insect and the vertebrate fauna, we explore both the local environment of early medieval Antwerp and its connections to the wider hinterland surrounding the town. Excavations in the Antwerp burg have revealed remarkably well preserved wooden trackways, houses, fences, and numerous finds, often related to artisanal activities, including bone, antler and metal working. Around 900 CE, a D-shaped earthen rampart was erected; it was subsequently fortified by a stone wall. The Antwerp burg area is considered a nucleus and catalyst for the urban development. Like many contemporary early urban sites, the macrofaunal remains are dominated by bones of domestic cattle and pigs. However, the presence of sizable numbers of wild mammals, including red deer, wild boar, and beaver, distinguishes the Antwerp burg sites from other contemporary sites such as Ipswich. A number of house structures were excavated within the D-shaped rampart area. A micromorphological analysis of micro-laminated layers of one of these structures was performed, revealing the evolution of its use within a single location. On top of the oldest ash deposit, a thick stabling horizon containing leaves, grass, wood fragments and animal dung was identified. The insect analysis from the stabling horizon confirmed that this deposit was primarily comprised of dung or stable manure, with stored hay or other plant matter also indicated. A high percentage presence of natural woodland indicators was also noted, suggesting that timber and wattle for buildings and trackways was sourced from such woodlands in close proximity to the early town. This is a virtually unique aspect for insect faunas from early towns in north and west Europe, with closest parallels coming from Novgorod, in Russia. The upper part of the sequence shows the presence of floors related to a more domestic use of space. This combined archaeological, macrofaunal, insect and micromorphological study suggests that early Antwerp already had a thriving market and artisanal quarter by the 10th century, with domestic animals stabled within the town for butchery or export, and wild resources being brought in for processing and craft working.